Effect of Fe, Ni, and Co on the hydrothermal liquefaction of Chinese herb residue for bio-oil production - Liu Liangbei; Guan Haibin; Chen Bingtong; Zhao Baofeng; Zhong Cunqing; Zhang Heming; Zhu Di; Bao Qinghe; Wulan Bari; Feng Xiangyu (Science and Technology for Energy Transition, 2024)
This study investigated the effects of reaction temperature (300–360 °C), reaction time (0–60 min), and the ratio of raw materials to solvent (1:5–1:15; g/mL) on the HydroThermal Liquefaction (HTL) of Chinese Herb Residues (CHR) for Bio-Oil (BO) production. Optimal HTL conditions for CHR were determined. To enhance both the yield and quality of BO, metal-modified catalysts including Fe/MCM-41, Co/MCM-41, and Ni/MCM-41 were prepared. These catalysts, after hydrogen reduction, loaded metal elements in their elemental state onto the carrier. Subsequently, CHR catalytic HTL experiments were conducted at 330 °C for 15 min with a ratio of 1:10 (g/mL). BO analysis was performed using EA, GC-MS, and FT-IR. Under the optimal HTL conditions (330 °C/15 min/1:10), the BO yield reached 24.57 wt.%, with a Higher Heating Value (HHV) of 25.96 MJ/kg. The major components of the BO included phenols, ketones, acids, and esters. In the catalytic HTL, Fe/MCM-41 (26.15 wt.%), Ni/MCM-41 (26.2 wt.%), and Co/MCM-41 (27.05 wt.%) catalysts each achieved higher BO yields. When using Ni/MCM-41 catalyst, the highest HHV of BO reached 32.01 MJ/kg, representing an 81% improvement over CHR HHV of 17.66 MJ/kg. Additionally, with Fe/MCM-41 catalyst, the lowest oxygen content in BO was 9.68%, and the selectivity for phenols and ketones was the highest, showing increases of 15.22% and 33.15%, respectively, reaching 44.13% and 24.5%. The results indicate that HTL can effectively convert high-moisture CHR into valuable products. Hydrogen-reduced metal-modified catalysts contribute significantly to increasing BO yield, promoting deoxygenation and hydrogenation reactions, and markedly improving HHV and the selectivity of chemical components, thereby effectively enhancing both the yield and quality of BO.